The Relationship Between Vitamin D Gene Polymorphisms and the Diagnosis of Prostate Cancer in Patients with High Prostate-Specific Antigen Value - HAKLAR, GONCAGÜL; TİNAY, İLKER (GALENOS YAYINCILIK, 2020)
Objective: To investigate the effects of vitamin D levels and vitamin D receptor (VDR) BsmI, FokI, TaqI, and ApaI gene polymorphisms on prostate cancer (PCa) diagnosis in Turkish men with high prostate-specific antigen (PSA) levels during screening. Materials and Methods: Patients who were admitted to the outpatient clinic with elevated PSA levels and were scheduled for transrectal prostate biopsy were included. Patients diagnosed with PCa were divided into two groups of either localized disease (low/intermediate/high risk) or metastatic disease for subgroup analysis. The control group comprised patients whose biopsies revealed benign pathologies. Blood samples were collected from each patient after 12 hours of fasting before the prostate biopsy. Vitamin D levels and VDR gene polymorphisms were determined by ECLIA method and restriction fragment length polymorphism analysis, respectively. Results: A total of 77 patients (PCa, 39; benign, 38) were included in the study. The frequencies of BsmI, FokI, TaqI, and ApaI genotypes for PCa and benign groups were evaluated. Vitamin D deficiency was detected in 88.6% and 94.9% of the benign and PCa groups, respectively (p=0.176). The FokI Ff and BsmI bb genotypes, and FokI FF and BsmI Bb genotypes were found to be more common in the PCa and benign groups, respectively. ApaI Aa and TaqI Tt were found to be more frequent in both groups. In patients with metastatic PCa; Bsml Bb genotype, Apal Aa genotype, and Taql Tt genotypes were found to be more common. Conclusion: Although Bsml Bb genotype, Apal Aa genotype, and Taql Tt genotypes were more commonly found in patients with metastatic PCa, further studies with increased sample sizes are needed to support this relationship in the Turkish PCa population.
Keywords: Prostate cancer; vitamin D; gene polymorphism; D-RECEPTOR GENE; ASSOCIATION; SUSCEPTIBILITY; METAANALYSIS; RISK; EXPRESSION; GROWTH